"Moment of Truth" in Educational Marketing. Factors That Contribute to the Decision Making on the Educational Market in Romania. (5th May 2015) - Glava, Catalin Cosmin; Glava, Adina Elena
Abstract: This paper represents an analysis of the concepts of educational marketing and educational market offers in Romania. The paper intends to underline the main actors involved on the Romanian educational market and their predilect manners of presenting themselves on the market. We present the role of the marketing initiatives in the context of the management of the educational institutions, as marketing is an intrinsic component and a function of the institutional marketing. We make a distinction between the general marketing and the educationally focused marketing, on the bases of the market segmenting principles, that are traditional marketing principles, yet relatively new in the educational field. We present results of a research on the factors that lead to decisions in parents or students' decision in choosing the school, in their relative order of importance. The research focused on the analysis of the factors which parents from Romania consider important when choosing a school in comparison with the factors recognized worldwide.